(untitled) (Contemporary Journal of Social Science Review, 2025)
This study investigates the relationship between sustainable tourism practices and economic growth in Pakistan by integrating the principles of endogenous growth theory with robust econometric modeling. Pakistan possesses significant but underutilized tourism resources, including natural landscapes, historical sites, and cultural heritage. However, its tourism sector faces persistent challenges such as political instability, poor infrastructure, and limited environmental planning. Using (International Monetary Fund, Pakistan Bureau of Statistics, World Bank) annual data from 1995 to 2021, this research employs ordinary least squares, autoregressive distributed lag bounds testing, and the vector error correction model to examine how tourism receipts, employment in tourism, political stability, and environmental sustainability influence real GDP. The empirical findings reveal a statistically significant and positive relationship between tourism receipts and GDP growth, reaffirming tourism’s role as a direct driver of economic development. Employment in the tourism sector also demonstrates a meaningful contribution to economic output by enhancing household income and stimulating local consumption. Political stability and environmental sustainability, while less impactful in the short run, are found to be crucial in maintaining long-run equilibrium and ensuring sustainability in the tourism sector through different tests and approaches as concluded in the findings paragraphs. The autoregressive distributed lag model confirms the existence of long-run cointegration among the variables, while the vector error correction model illustrates a moderate but stable adjustment toward long-run equilibrium. This study underscores the need for Pakistan to adopt a coordinated, sustainability-focused tourism policy that emphasizes investment in infrastructure, environmental regulation, institutional reform, and community engagement. It advocates for shifting from volume-based to value-driven tourism strategies. The strategy uses green practices, digital promotion, and decentralized governance to maximize benefits. The findings contribute empirical and policy insights for integrating tourism into national development agendas. Ultimately, sustainable tourism emerges as a strategic avenue for comprehensive, resilient, and environmentally sound economic growth in Pakistan.